2023
DOI: 10.3389/fbinf.2023.1120370
|View full text |Cite
|
Sign up to set email alerts
|

Before and after AlphaFold2: An overview of protein structure prediction

Abstract: Three-dimensional protein structure is directly correlated with its function and its determination is critical to understanding biological processes and addressing human health and life science problems in general. Although new protein structures are experimentally obtained over time, there is still a large difference between the number of protein sequences placed in Uniprot and those with resolved tertiary structure. In this context, studies have emerged to predict protein structures by methods based on a tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 55 publications
4
55
0
Order By: Relevance
“…The motivation behind protein language models is to treat amino acids and protein sequences as words/symbols and sentences in NLP, respectively. Based on the assumption that similar semantics come from amino acids appearing in similar contexts, protein language models can learn evolutionary and functional patterns solely from amino acid sequences . ESMFold, developed by Meta Fundamental AI Research Protein Team (FAIR), is an efficient end-to-end sequence-to-structure method based on a language model.…”
Section: Advances In Protein Structure Prediction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation behind protein language models is to treat amino acids and protein sequences as words/symbols and sentences in NLP, respectively. Based on the assumption that similar semantics come from amino acids appearing in similar contexts, protein language models can learn evolutionary and functional patterns solely from amino acid sequences . ESMFold, developed by Meta Fundamental AI Research Protein Team (FAIR), is an efficient end-to-end sequence-to-structure method based on a language model.…”
Section: Advances In Protein Structure Prediction Methodsmentioning
confidence: 99%
“…For the MSA-free end-to-end methods, the pretrained deep learning models are usually protein language models which drive from natural language processing (NLP). 33 The motivation behind protein language models is to treat amino acids and protein sequences as words/symbols and sentences in NLP, respectively. Based on the assumption that similar semantics come from amino acids appearing in similar contexts, protein language models can learn evolutionary and functional patterns solely from amino acid sequences.…”
Section: Advances In Protein Structure Prediction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, it appears that AF2 is unable to predict defects in protein structures caused by mutations [ 79 ]. One investigation showed that differences between mutated and wild-type structures predicted by AlphaFold were extremely small [ 80 ].…”
Section: Critique Of Alphafoldmentioning
confidence: 99%
“…While these studies are promising, the dogma remains that AlphaFold2 is not able to predict the effect of point mutations. 1215…”
Section: Introductionmentioning
confidence: 99%